PENGARUH BAURAN PROMOSI (PROMOTION MIX) TERHADAP KEPUTUSAN PEMILIHAN LEMBAGA PENDIDIKAN BAHASA INGGRIS INTERNATIONAL LANGUAGE FOUNDATION (ILF) DI LAMONGAN - jurnalpps pps; Ahmad Latif (Prodi Magister Manajemen Universitas Wijaya Putra, 2020)
ABSTRACT The purpose of the research is to determine the effect of promotion mix which is Advertising, Sales Promotion, Personal Selling, Public Relations, Direct Marketing on Regestration decision of English Centre of International Language Foundation (ILF) Lamongan. The population of the research was the parents of English Centre of International Language Foundation (ILF) Lamongan. The number of sample was 57 parents. The number of the questionnaire was 31 and used Likert scale. The research was conducted on February 2018 until Mey 2019. The research used multiple regression analysis and also used validity ÔÇô reliability in each statement. Hypothesis testing was performed using F test, t test, correlation coefficient of determintation and partial determination coefficient. The research used classicial assumption test, which consisted of multiconlinearity test, heteroskedasity test, normality test and liniearity test. The result was the Sales Promotion was having a significant effect to Regestration Decision. However, the Advertising, Personal Selling, Publilc and Direct Marketin had no significant effect to Buying Decision. Keywords: advertising, sales promotion, personal selling, public relations, direct marketing, regestration decision